Functions and principles of tort law: the art. 927 § único of the Brazilian Civil Code - Püschel, Flavia Portella (2005)
THIS PAPER HAS THE GOAL TO REFLECT UPON POSSIBLE GUIDELINES FOR THE INTERPRETATION OF ART. 927, PARÁGRAFO ÚNICO, OF THE NEW BRAZILIAN CIVIL CODE, WHICH HAS INTRODUCED A GENERAL STRICT TORT LIABILITY RULE INTO BRAZILIAN LAW. IN ORDER TO DO THAT, THE AUTHOR ANALYZES THE FUNCTIONS NORMALLY ATTRIBUTED DO TORT LIABILITY, AS WELL AS THE PRINCIPLES DEVELOPED TO JUSTIFY STRICT LIABILITY IN GENERAL.